RELATIONSHIP OF ORGANIZATIONAL RESOURCES TO PRE-ANALYTIC ERRORS IN BANDUNG CITY PUSKESMAS LABORATORY - Suci Rizki Nurul Aeni (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2022)
Background. Lack of awareness about the role of laboratory services in many developing countries causes a lack of resources which is the main factor that affects the poor quality of laboratory services. Quality control aims to reduce or minimize errors that occur in the laboratory. The laboratory error ranged from 0.012-0.6%. Errors that occur in the pre-analytic stage are the largest, reaching 60-70% of the total laboratory errors. Pre-analytical error data from one of the Puskesmas laboratories in Bandung is 4.7%. Destination. To find out the description of organizational resources, description of pre-analytical errors and to determine the relationship of organizational resources to pre-analytical errors in the Bandung City Health Center Laboratory. Method. This research is a correlation analytic research. The research subjects were laboratory officers at the Bandung City Health Center Laboratory as many as 20 respondents. The resource variable was measured using a questionnaire and the pre-analytic error variable was derived from secondary data. Results. The results of this study indicate that the organizational resources at the Bandung City Health Center Laboratory are 65% quite good, 30% good and 5% not good. Pre-analytical errors in the Bandung City Health Center Laboratory, as much as 20% did not have pre-analytic errors, as many as 80% had pre-analytical errors. There is no relationship between organizational resources and pre-analytic errors in the Bandung City Health Center Laboratory (Sig. 2-tailed 0.422). Conclusion. Most (65%) of Bandung City Health Center Laboratories have good organizational resources. Pre-analytical errors in the Bandung City Health Center Laboratory varied between 0.10-27.03%. There is no relationship between organizational resource variables and pre-analytic errors in the Bandung City Health Center Laboratory.